A membrane protein based biosensor: Use of a phosphate – H + symporter membrane protein (Pho84) in the sensing of phosphate ions - Basheer, Shabana; Samyn, Dieter; Hedström, Martin; Thakur, Munna Singh; Persson, Bengt L.; Mattiasson, Bo (Biosensors & bioelectronics, 2011)
A label free biosensor for direct detection of inorganic phosphate based on potential-step capacitance measurements has been developed. The high-affinity Pho84 plasma membrane phosphate/proton symporter of Saccharomyces cerevisiae was used as a sensing element. Heterologously expressed and purified Pho84 protein was immobilized on a self-assembled monolayer (SAM) on a capacitance electrode. Changes in capacitance were recorded upon exposure to phosphate compared to the control substance, phosphate analogue methylphosphonate. Hence, even without the explicit use of lipid membranes, the Pho84 membrane protein could retain its capacity of selective substrate binding, with a phosphate detection limit in the range of the apparent in vivo K m . A linear increase in capacitance was monitored in the phosphate concentration range of 5–25 μM. The analytical response of the capacitive biosensor is in agreement with that the transporter undergoes significant conformational changes upon exposure to inorganic phosphate, while exposure to the analogue only causes minor responses.